A multicenter study on practices and related factors of traditional medicinal plant use during pregnancy among women receiving antenatal care in East Gojjam Zone, Northwest Ethiopia - Wondemagegn, Amsalu Taye; Seyoum, Girma (Frontiers in Public Health, 2023)
Background Little is known about the practice of traditional medicinal plant use, especially during pregnancy in Ethiopia. Moreover, there has been no previous studies conducted on practices and related factors of medicinal plant use among pregnant women in Gojjam, northwest Ethiopia. Methods A multicentered facility-based cross-sectional study was conducted from July 1 to 30 2021. A total of 423 pregnant mothers receiving antenatal care were included in this study. To recruit study participants, multistage sampling techniques were used. Data were collected using a semi-structured interviewer-administered questionnaire. SPSS version 20.0 statistical package was used for statistical analysis. Univariable and multivariable logistic regression analysis was performed to identify factors related to the medicinal plants' utilization status in pregnant mothers. The study results were presented in both descriptive statistics (percents, tables, graphs, mean, and dispersion measurements like standard deviation) and inferential statistics (odds ratio). Results The magnitude of traditional medicinal plants' utilization during pregnancy was 47.7% (95%CI: 42.8–52.8%). Pregnant mothers residing in rural areas [Adjusted Odds Ratio (AOR) = 3.13; 95% Confidence Interval (CI):1.53, 6.41], who are illiterate (AOR = 2.99; 95%CI:1.097, 8.17), have illiterate husbands (AOR = 3.08; 95%CI:1.29, 7.33), married farmers (AOR = 4.92; 95%CI:1.87, 12.94), married merchants (AOR = 0.27; 95%CI:0.09, 0.78), have a divorced and widowed marital status (AOR = 3.93; 95%CI:1.25, 12.395), have low antenatal care visits (AOR = 4.76; 95%CI:1.93, 11.74), substance use history (AOR = 7.21; 95%CI:3.49, 14.9), and used medicinal plants in previous pregnancy (AOR = 4.06; 95%CI:2.03, 8.13) had statistically significant association with medicinal plant use during current pregnancy. Conclusions The present study revealed that a relatively large number of mothers used medicinal plants of various types during their current pregnancy. Area of residence, maternal educational status, husband's education level, husband's occupation status, marital status, number of antenatal care visits, use of medicinal plants in previous pregnancies, and substance use history were among the factors which were significantly associated with the use of traditional medicinal plants during the current pregnancy. Overall, the current finding provides scientific evidence useful for health sector leaders and healthcare professionals on the utilization of unprescribed medicinal plants during pregnancy and the factors associated with the utilization of the plants. Hence, they may consider creating awareness and providing advice on the careful use of unprescribed medicinal plants among pregnant mothers, especially those residing in rural areas, who are illiterate, who have divorced and widowed marital status, and who have a previous history of herbal and substance use. This is because using traditional medicines without prior discussion with a healthcare expert may harm pregnant mothers and their unborn child, as the safety of the utilized plants in the current study area is not scientifically proven. Prospective studies which need to confirm the safety of the plants used are recommended mainly in the present study area.